IMPLEMENTASI ONE CHANNEL SYSTEM (OCS) PADA MEMORANDUM OF UNDERSTANDING TENTANG PENETAPAN DAN PERLINDUNGAN PEKERJA MIGRAN SEKTOR DOMESTIK: DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - NIM. A1011201109, JOSEF PARTOGI GULTOM (Jurnal Fatwa Hukum, 2024)
Abstract                       Malaysia is one of the most attractive countries for Indonesian migrant workers. In this case, the governments of Indonesia and Malaysia have signed a Memorandum of Understanding (MoU) on "Placement and Protection of Indonesian Migrant Workers in the Domestic Sector in Malaysia" in April 2022. The MoU stipulates that the recruitment and protection of Indonesian migrant workers in the domestic sector uses the One Channel System (OCS) which has been established by both parties. So that Indonesian migrant workers who want to work in the domestic sector must fulfill the requirements set out in the MoU. This system is useful for tracking Indonesian migrant workers in Malaysia so that they can fulfill the rights of these workers such as wages, workplaces to their health.                       This research uses normative juridical research methods with a descriptive nature. The type of research used is secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials collected through literature studies (library research) which are then analyzed with qualitative normative data analysis methods.                       In an effort to provide protection for migrant workers and help the country's economy, the One Channel System is one of the strategies of the government as outlined in the MoU on the Placement and Protection of Migrant Workers. Therefore, in an effort to provide protection for migrant workers and efforts to improve the country's economy, this MoU provides facilities and facilities provided by the government for migrant workers, if the Malaysian recruitment agency needs workers, the government then provides easy regulation for migrant workers.The establishment of a Memorandum of Understanding Indonesia and Malaysia is one of the efforts made by both countries in an effort to provide protection for migrant workers through the One Channel System, as well as the rights and responsibilities regulated by each party appointed to be involved in it. However, in its implementation, Malaysia still uses the migrant worker placement system outside the established agreement.Keywords:   Memorandum of Understanding (MoU), One Channel System, Migrant Workers  AbstrakMalaysia merupakan salah satu negara yang cukup menarik bagi pekerja migran indonesia. Dalam hal ini, pemerintah Indonesia dan Malaysia telah menandatangani Memorandum of Understanding (MoU) tentang "Penempatan dan Perlindungan Pekerja Migran Indonesia Sektor Domestik di Malaysia" pada bulan April 2022. Pada MoU tersebut menetapkan bahwa perekrutan dan perlindungan pekerja migran Indonesia dalam sektor domestik menggunakan Sistem Satu Saluran atau One Channel System (OCS) yang telah ditetapkan oleh kedua belah pihak. Sehingga bagi pekerja migran Indonesia yang ingin bekerja di sektor domestik harus memenuhi persyaratan yang telah ditetapkan dalam MoU tersebut. Sistem ini berguna untuk melacak pekerja migran Indonesia di Malaysia sehingga dapat memenuhi hak dari pekerja tersebut seperti upah, tempat kerja hingga kesehatan mereka.                       Penelitian skripsi menggunakan metode penelitian yuridis normatif dengan bersifat deskriptif. Jenis penelitian yang digunakan adalah data sekunder berupa bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier yang dikumpulkan melalui studi pustaka (library research) yang selanjutnya dianalisis dengan metode analisis data normative kualitatif.                       Dalam upaya memberikan perlindungan bagi pekerja migran serta membantu perkonomian negara, One Channel System merupakan salah satu strategi dari pemerintah yang dituangkan dalam MoU Penempatan dan Perlindungan Pekerja Migran. Maka dari itu dalam upaya memberikan perlindungan pekerja migran serta upaya untuk meningkatkan perekonomian negara pada MoU ini memberikan fasilitas dan kemudahan yang diberikan oleh pemerintah bagi para pekerja migran, bila agensi perekrutan Malaysia membutuhkan Tenaga kerja, pemerintah kemudian memberikan kemudahan regulasi bagi para pekerja migran. Pembentukan MoU yang dilakukan antara Indonesia dan Malaysia merupakan salah satu upaya yang dilakukan oleh kedua belah negara dalam upaya memberikan perlindungan terhadap pekerja migran melalui One Channel System atau Sistem satu kanal, serta adanya hak dan tanggung jawab yang diatur dari setiap pihak yang ditunjuk untuk terlibat di dalamnya. Namun dalam pelaksaannya pihak Malaysia masih menggunakan sistem penempatan pekerja migran diluar kesepakatan yang telah ditetapkan.Kata Kunci: Memorandum of Understanding (MoU), One Channel System, Pekerja Migran